Engineering Point Mutant and Epitope‐Tagged Alleles in Mice Using Cas9 RNA‐Guided Nuclease. Issue 1 (30th March 2018) - Gertsenstein, Marina; Nutter, Lauryl M. J.
Abstract: Mice carrying patient‐associated point mutations are powerful tools to define the causality of single‐nucleotide variants to disease states. Epitope tags enable immuno‐based studies of genes for which no antibodies are available. These alleles enable detailed and precise developmental, mechanistic, and translational research. The first step in generating these alleles is to identify within the target sequence—the orthologous sequence for point mutations or the N or C terminus for epitope tags—appropriate Cas9 protospacer sequences. Subsequent steps include design and acquisition of a single‐stranded oligonucleotide repair template, synthesis of a single guide RNA (sgRNA), collection of zygotes, and microinjection or electroporation of zygotes with Cas9 mRNA or protein, sgRNA, and repair template followed by screening of born mice for the presence of the desired sequence change. Quality control of mouse lines includes screening for random or multicopy insertions of the repair template and, depending on sgRNA sequence, off‐target mutations introduced by Cas9. © 2018 by John Wiley & Sons, Inc.